alogorithm

Asked by  | 13th Feb, 2009, 10:17: PM

Expert Answer:

Let the first term be a and the common difference be d.

Then,

nth term is given by the formula,

nth term = a+(n-1)d

So

p the term = a+(p-1)d

and

 qth term =a+(q-1)d

According to question,pth term is q and qth term is p.

So,

 

a+(p-1)d=q

a+(q-1)d=p

So,

 (p+q)th term

=a+(p+q-1)d

At this stage you can substitute the values.

Answered by  | 14th Feb, 2009, 09:13: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.